Privatização, mudança organizacional e novas relações de trabalho: um caso do setor de energia elétrica. - Alves, Agda de Fátima (Universidade Federal de São Carlos, 2004)
This study analyses the process of organizational change and the new work relations decurrent of the privatization of eletric sector companies in São Paulo. The privatization of the State companies appears as an important mark in that process of change, because represent the necessity of to adapt the companies towards the new scenery occasioned by aperture of brazilian economy. The study focused on the point of view of an electric energy distributer company s employees, through twenty interviews with employees in various posts. These changes transformed the company organization and also brought consequences to the work relations and society. The centre of discussion was the appearing of new work relations, which was felt by workers as negative consequences, at least in this prime moment of adaptation to the new standard of life.
Keywords: Administração de pessoal; Desenvolvimento organizacional; Relações de trabalho no setor elétrico; Privatização; Mudança Organizacional; Privatization; Electric sector; Organizational change; Work relations; ENGENHARIAS::ENGENHARIA DE PRODUCAO